The Mystery Of The Cupboard - Lynne Reid Banks (U.S.A HarperCollins Publishers, 1993)
In the fourth book in Bank's acclaimed INDIAN IN THE CUPBOARD saga, Omri and his family move to an old farmhouse, where he finds an ancient notebook that reveals a family secret-and the mysterious origins of his magical cupboard.
Keywords: Classic -- Fantasy